Inflammasomes and their roles in arthritic disease pathogenesis - Yang, Gabsik; Kang, Han Chang; Cho, Yong-Yeon; Lee, Hye Suk; Lee, Joo Young (Frontiers in Molecular Biosciences, 2022)
The inflammasome is a molecular platform that is created in the cytosolic compartment to mediate the host immunological response to cellular injury and infection. Caspase-1 may be activated by the inflammasome, which leads to the generation of the inflammatory cytokines interleukin-1β (IL-1β) and IL-18 and the beginning of pyroptosis, which is a type of proinflammatory cell death. Scientists have identified a number of different inflammasomes in the last two decades. The NLRP3 inflammasome has been studied the most, and its activity may be triggered by a broad range of different inducers. However, activation of the NLRP3 inflammasome in a manner that is not properly controlled is also a factor in the etiology of many human illnesses. Accumulating evidence indicates that the NLRP3 inflammasome plays a significant role in the innate and adaptive immune systems and the development of various arthritic illnesses, such as rheumatoid arthritis, ankylosing spondylitis, and gout. The present review provides a concise summary of the biological properties of the NLRP3 inflammasome and presents the fundamental processes behind its activation and control. We discuss the role of the inflammasome in the pathogenesis of arthritic diseases, such as rheumatoid arthritis, ankylosing spondylitis, and gout, and the potential of newly developed therapies that specifically target the inflammasome or its products for the treatment of inflammatory diseases, with a particular emphasis on treatment and clinical application.